1999
DOI: 10.3109/10428199909145725
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype of Bone Marrow Mast Cells in Indolent Systemic Mast Cell Disease in Adults

Abstract: One of the major advances in the histological diagnosis of bone marrow (BM) involvement in mastocytosis has been the specific immunohistochemical detection of tryptase on most cells (MC), which has shown to be of great diagnostic value, especially in cases of malignant mastocytosis. On the other hand, recent studies have clearly shown that bone marrow mast cells can be specifically identified and accurately enumerated using multiparametric flow cytometry, which allow a systematic analysis of the immunophenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 43 publications
2
25
0
1
Order By: Relevance
“…[73][74][75][76] The surrogate hCD2 marker introduced with the NRASV12 transgene may contribute to the development of the ASM phenotype described here. Although the intracellular portion of CD2 has been deleted, the extracellular domain may engage antigen-presenting cells in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75][76] The surrogate hCD2 marker introduced with the NRASV12 transgene may contribute to the development of the ASM phenotype described here. Although the intracellular portion of CD2 has been deleted, the extracellular domain may engage antigen-presenting cells in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…(Source: Bodni et al, 2003;Diaz-Agustin et al, 1999;Escribano et al, 1995Escribano et al, , 1997Escribano et al, , 1998bEscribano et al, , 1998cEscribano et al, , 1998dEscribano et al, , 1999Escribano et al, , 2001Escribano et al, , 2002Escribano et al, , 2006Nun˜ez et al, 2002;Orfao et al, 1996;Pardanani et al, 2004;Teodosio et al, 2010;Valent et al, 2001b. (Source: Bodni et al, 2003;Diaz-Agustin et al, 1999;Escribano et al, 1995Escribano et al, , 1997Escribano et al, , 1998bEscribano et al, , 1998cEscribano et al, , 1998dEscribano et al, , 1999Escribano et al, , 2001Escribano et al, , 2002Escribano et al, , 2006Nun˜ez et al, 2002;Orfao et al, 1996;Pardanani et al, 2004;Teodosio et al, 2010;Valent et al, 2001b.…”
Section: Activated MC Immunophenotypeunclassified
“…Apart from the aberrant expression of CD2 and CD25, quantitative FCM studies of BMMC from indolent systemic mastocytosis (ISM) [10], aggressive systemic mastocytosis, and isolated BM mastocytosis [Escribano et al, unpubl. data] have shown that, similarly, BMMC from these conditions also show a lower expression of the CD117 antigen and abnormally high levels of expression of the CD29 and CD33 antigens [11, 12, 13]. Interestingly, three activation-associated antigens (CD35, CD63 [14], and CD69 [15]) have been reported as overexpressed in MC from mastocytosis as well.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, three activation-associated antigens (CD35, CD63 [14], and CD69 [15]) have been reported as overexpressed in MC from mastocytosis as well. Overall, these unique phenotypic features are of great relevance for the differential diagnosis of BM involvement in patients with mastocytosis, since almost no overlap was found between the levels of expression on BMMC from ISM and aggressive systemic mastocytosis patients and those found in other groups of individuals [revised in 11, 12, 13]. Additional phenotypic differences between normal BMMC and BMMC from mastocytosis patients include overexpression of complement-related antigens such as CD11c, CD58 [Núñez et al, unpubl.…”
Section: Introductionmentioning
confidence: 99%